Navigating Religion Online: Jewish and Muslim Responses to Social Media - Ferguson, Jauhara (Religions, 2021)
Although social media use among religious communities is proliferating, significant gaps remain in our understanding of how religious minorities perceive social media in relation to their faith and community. Thus, we ask how individuals use religion to frame moral attitudes around social media for Jews and Muslims. Specifically, how does social media shape understandings of community? We analyze 52 interviews with Jews and Muslims sampled from Houston and Chicago. We find that Jews and Muslims view social media as a “double-edged sword”—providing opportunities to expand intracommunal ties and access to religious resources, while also diluting the quality of ties and increasing exposure to religious distractions. These findings help us understand what it is about being a religious minority in the US that might shape how individuals engage with social media. Moreover, they suggest that social media may be transforming faith communities in less embodied ways, a topic that is of particular relevance in our pandemic times.